Karakter Oseanografi Perairan Makassar Terkait Zona Potensial Penangkapan Ikan Pelagis Kecil pad Musim Timur - J, Abd Rasyid; N, Nurjannah; Burhanuddin, Andi Iqbal; Hatta, Muh. (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The availability of fish in the fishing area is influenced by oceanography condition. In Makassar coastal waters, potential area of small pelagic fish is the main information for the fisherman. Purpose of this research is to provide information of oceanographic characteristics which connected with fishing potential area on east season. This research was conducted during May-December 2012, using field and secondary data. Potential area determination was analyzed by using polynomial model. Distribution of oceanographic factors was analyzed by SMS and surfer. Makassar has continent as well as island areas (12 islands). Oceanographic conditions indicate tidal current velocity of 0.08 m/s and ebb currents from 0.05 to 0.30 m/s. Sea surface temperatures in the spring waters east of Makassar were in the range of 26 -31oC. The concentration of chlorophyll-a occurred between 0.0 and 1.0 mg/m3, oceanographic conditions in July and August 2012 are relatively similar. Potential zone for small pelagic fish species in June, July, and August are in the waters around the islands - northern part of the island of Makassar and from the island to Lanyukkang Lumu-Lumu island.Â Â Â